Pengaruh Profitabilitas Dan Manajemen Laba Terhadap Tax Avoidance Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Pada Tahun 2018-2022 - Fariha, Siti; Zahran, Wahidin Septa (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The purpose of this study was to determine how much influence profitability, and earnings management have on tax avoidance. The population used in this study are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The research method used is descriptive quantitative and the sample is determined using purposive sampling technique and obtaining a sample of 23 companies based on predetermined criteria, with the help of IBM SPSS Statistics 25 software the amount of data will be tested with the classical assumption test, multiple linear regression test and hypothesis testing. The results of this study indicate that profitability has a positive and significant effect on tax avoidance, earnings management has a positive and significant effect on tax avoidance, and for simultaneously profitability, and earnings management have a significant effect on tax avoidance.